Phosphide-coated sodium ion battery positive electrode material, preparation method thereof and sodium ion battery
By using phosphide coating technology on the positive electrode material of sodium ion battery, the serious structural changes in traditional materials during circulation are solved, and the first discharge capacity and cycle stability of the battery are significantly improved, achieving better rate performance and long-term stability.
Patent Information
- Application Number
- CN202411893791.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-05-02
AI Technical Summary
The structure of the positive electrode material of traditional sodium ion battery changes severely during the cycle process, resulting in low first discharge capacity, poor cycle stability and insufficient rate performance, hindering the commercialization process of sodium ion battery.
Using phosphide coating technology, the transition metal source, 2-methylimidazole and the positive electrode material matrix are dispersed in a solvent, and then sintered with the elemental phosphorus in a protective atmosphere after standing to form a uniform phosphide coating layer, improving the electronic conductivity and ion diffusion kinetics of the material.
The first discharge capacity and cycle stability of the positive electrode material of sodium ion battery are significantly improved, the stability of the material structure is enhanced, and the rate performance and long-term stability of the battery are improved.
Smart Images

Figure CN119920872A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a sodium ion battery positive electrode material and a preparation method and application thereof. Background Art
[0002] The performance of sodium ion battery cathode materials directly affects the overall performance of the battery, especially the initial discharge capacity, cycle stability and rate performance of the battery. x Although MnO2 has a high theoretical specific capacity, it often faces problems such as low first discharge capacity, poor cycle stability and insufficient rate performance in practical applications. These problems are mainly due to the structural changes of the cathode material during the cycle, such as volume expansion, phase transition and ion diffusion kinetics limitation, which seriously restrict the commercialization of sodium-ion batteries.
[0003] In order to overcome the above technical defects, researchers have tried a variety of strategies, including optimizing material structure, introducing doping elements, preparing nanomaterials, and surface coating. In particular, phosphide coating technology can effectively improve electron transport performance and ion diffusion kinetics, and is considered to be an effective way to improve the performance of sodium ion battery positive electrode materials. For example, CN115275156A discloses a composite positive electrode material for a sodium ion battery, including a core and a shell coated outside the core, wherein the core is a transition metal sodium oxide, and the shell is a transition metal sodium phosphide; the composite positive electrode material has a high discharge capacity and first effect, which can improve the energy density of the battery, reduce self-discharge, and extend the cycle life of the battery. However, the existing phosphide coating process still has certain limitations. First, the uniformity and thickness control of the coating layer are a major challenge, and the uneven coating layer may lead to unstable battery performance. Secondly, the high temperature reaction during the coating process may cause the positive electrode material structure to be partially destroyed, affecting the long-term stability of the battery. In addition, the selection of coating materials is also a difficulty. Summary of the invention
[0004] In view of the problems existing in the prior art, the first object of the present invention is to provide a phosphide-coated sodium ion battery positive electrode material; the second object of the present invention is to provide a method for preparing a phosphide-coated sodium ion battery positive electrode material; the third object of the present invention is to provide a sodium ion battery.
[0005] To achieve the above objectives, the present invention provides the following specific technical solutions.
[0006] In a first aspect, the present invention provides a phosphide-coated sodium ion battery positive electrode material, comprising a positive electrode material matrix and a coating material coated on at least a portion of the surface of the positive electrode material matrix; the chemical formula of the positive electrode material matrix is Na y Mnz O2, 0.67<y<1, 0<z<1; the coating material includes MP, and M is at least one of Ni, Co, and Mn.
[0007] In a second aspect, the present invention provides a method for preparing a phosphide-coated sodium ion battery positive electrode material, comprising: Dispersing a transition metal source, 2-methylimidazole, and a cathode material matrix in a solvent, allowing the mixture to stand, performing solid-liquid separation, and drying the solid phase to obtain a precursor; The precursor and elemental phosphorus are sintered under a protective atmosphere to obtain a phosphide-coated sodium ion battery positive electrode material; The transition metal source is at least one of a nickel source, a cobalt source and a manganese source.
[0008] In a third aspect, the present invention provides a sodium ion battery, comprising the aforementioned phosphide-coated sodium ion battery positive electrode material or the phosphide-coated sodium ion battery positive electrode material prepared by the aforementioned preparation method.
[0009] The beneficial effects that can be achieved by one or more of the above technical solutions of the present invention will be presented through specific implementation methods or specific examples. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 This is the XRD diagram of the coated and modified positive electrode material obtained in Example 1.
[0011] Figure 2 This is the SEM image of the coated and modified positive electrode material obtained in Example 1.
[0012] Figure 3 This is the XRD diagram of the coated and modified positive electrode material obtained in Example 2.
[0013] Figure 4 This is the SEM image of the coated and modified positive electrode material obtained in Example 2. DETAILED DESCRIPTION
[0014] In a first aspect, some embodiments of the present invention provide a phosphide-coated sodium ion battery positive electrode material, comprising a positive electrode material matrix and a coating material coated on at least a portion of the surface of the positive electrode material matrix; the chemical formula of the positive electrode material matrix is Na y Mn z O2, 0.67<y<1, 0<z<1; the coating material includes MP, and M is at least one of Ni, Co, and Mn.
[0015] In some specific embodiments, the molar ratio of the positive electrode material matrix to the coating material is 1-x:x, 0.3≤x<0.7. When the molar ratio of the positive electrode material matrix to the coating material is within this range, the coating effect is the best.
[0016] In a second aspect, some embodiments of the present invention provide a method for preparing a phosphide-coated sodium ion battery positive electrode material, comprising: The transition metal source, 2-methylimidazole, and the cathode material matrix are dispersed in a solvent, allowed to stand, solid-liquid separated, and the solid phase dried to obtain a precursor; the chemical formula of the cathode material matrix is Na y Mn z O2, 0.67<y<1, 0<z<1; The precursor and elemental phosphorus are sintered under a protective atmosphere to obtain a phosphide-coated sodium ion battery positive electrode material; The transition metal source is at least one of a nickel source, a cobalt source and a manganese source.
[0017] Uniformly coating the surface of the positive electrode material with phosphide can not only increase the electronic conductivity of the material, but also improve the ion transmission path, which can significantly increase the initial discharge capacity of the battery. The addition of the phosphide coating layer effectively strengthens the stability of the material structure and reduces the structural changes during the cycle, thereby greatly improving the cycle stability.
[0018] In some specific embodiments, the nickel source is at least one of nickel chloride, nickel oxide, and nickel carbonate; the cobalt source is at least one of cobalt chloride, cobalt oxide, and cobalt carbonate; and the manganese source is at least one of manganese chloride, manganese oxide, and manganese carbonate.
[0019] In some specific embodiments, the molar ratio of the transition metal in the transition metal source, 2-methylimidazole, and the positive electrode material matrix is 1:3:6.
[0020] In some specific embodiments, the solvent is water or methanol.
[0021] In some specific embodiments, the standing time is 12 to 24 hours.
[0022] In some specific embodiments, the molar ratio of the positive electrode material matrix and the phosphorus source in the precursor is 1:5-10.
[0023] In some specific embodiments, during sintering, a protective atmosphere is continuously introduced; the phosphorus source and the precursor are placed in sequence along the flow direction of the protective atmosphere.
[0024] The phosphorus source and the precursor are sequentially arranged along the flow direction of the protective atmosphere, that is, a vapor deposition reaction occurs during the sintering process. Vapor deposition can ensure the uniformity of the coating layer, optimize the ion diffusion kinetics, and enable the material to maintain good performance under high-rate discharge conditions.
[0025] In some specific embodiments, the protective atmosphere is at least one of nitrogen, argon, and helium.
[0026] In some specific implementation methods, the sintering temperature is 300-500° C.; the sintering time is 2-5 hours; and the sintering heating rate is 3-6° C. / min.
[0027] In a third aspect, the present invention provides a sodium ion battery, comprising the aforementioned phosphide-coated sodium ion battery positive electrode material or the phosphide-coated sodium ion battery positive electrode material prepared by the aforementioned preparation method.
[0028] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0029] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0030] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0031] Example 1 First, manganese carbonate and sodium carbonate were mixed in a molar ratio of 2.5:1.2, put into a mortar and ground evenly, and then ball-milled at 800 rpm for 7 hours. Subsequently, the ball-milled material was transferred to a tube furnace under air atmosphere and calcined at a high temperature of 900°C for 20 hours to obtain the positive electrode material.
[0032] Nickel chloride, 2-methylimidazole and the positive electrode material were mixed in a molar ratio of 1:3:6, dispersed in deionized water and allowed to stand for 16 hours, then centrifuged, and the solid phase was dried to obtain a precursor.
[0033] Nitrogen was continuously introduced into the tube furnace, the precursor was placed in the tube furnace, and phosphorus was placed in the upstream wind direction of the precursor. The molar ratio of the precursor to the phosphorus was 1:7. The tube furnace was heated to 450°C at a heating rate of 5°C / min and kept warm for 3h, and then cooled to room temperature to obtain the coated modified positive electrode material.
[0034] The coated modified positive electrode material obtained in this embodiment was analyzed by X-ray powder diffraction, and the results were as follows: Figure 1 As shown, there are O3 phase and nickel phosphide in its physical phase, indicating that the phosphide coating on the surface of the positive electrode material is successful.
[0035] The coated modified positive electrode material obtained in this embodiment was scanned by a scanning electron microscope, and the result is as follows: Figure 2 As shown, its surface coating layer is in the form of nanosheets, which is consistent with theoretical expectations and indicates that the phosphide is uniformly coated on the surface of the positive electrode material.
[0036] Comparative Example 1 Manganese carbonate and sodium carbonate were mixed in a molar ratio of 2.5:1.2, ground evenly in a mortar, and then ball-milled at 800 rpm for 7 hours. Subsequently, the ball-milled material was transferred to a tube furnace under air atmosphere and calcined at 900°C for 20 hours to obtain a positive electrode material.
[0037] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the phosphorus element is replaced by sodium phosphate; and the precursor is mixed with sodium phosphate and then placed in a tube furnace.
[0038] Example 2 First, manganese oxide and sodium hydroxide were mixed in a molar ratio of 3:1, put into a mortar and ground evenly, and then ball-milled at a speed of 600 rpm for 9 hours. Subsequently, the ball-milled material was transferred to a tube furnace under air atmosphere and calcined at a high temperature of 800°C for 18 hours to obtain the positive electrode material.
[0039] Manganese oxide, 2-methylimidazole and the positive electrode material were mixed in a molar ratio of 1:3:6, dispersed in methanol and allowed to stand for 24 hours, then centrifuged, and the solid phase was dried to obtain a precursor.
[0040] Nitrogen was continuously introduced into the tube furnace, the precursor was placed in the tube furnace, and phosphorus was placed in the upstream wind direction of the precursor. The molar ratio of the precursor to the phosphorus was 1:8. The tube furnace was heated to 400°C at a heating rate of 4°C / min and kept warm for 4h, and then cooled to room temperature to obtain the coated modified positive electrode material.
[0041] The coated modified positive electrode material obtained in this embodiment was analyzed by X-ray powder diffraction, and the results were as follows: Figure 3 As shown, there are O3 phase and manganese phosphide in its physical phase, indicating that the phosphide coating on the surface of the positive electrode material is successful.
[0042] The coated modified positive electrode material obtained in this embodiment was scanned by a scanning electron microscope, and the result is as follows: Figure 4 As shown, it is an irregular secondary spherical morphology, indicating that the phosphide is evenly coated on the surface of the positive electrode material.
[0043] Example 3 First, manganese carbonate and sodium nitrate were mixed in a molar ratio of 2:1.5, put into a mortar and ground evenly, and then ball-milled at a speed of 900 rpm for 8 hours. Subsequently, the ball-milled material was transferred to a tube furnace under air atmosphere and calcined at a high temperature of 950°C for 22 hours to obtain the positive electrode material.
[0044] Nickel carbonate, 2-methylimidazole and the positive electrode material were mixed in a molar ratio of 1:3:6, dispersed in deionized water and allowed to stand for 20 hours, then centrifuged, and the solid phase was dried to obtain a precursor.
[0045] Nitrogen was continuously introduced into the tube furnace, the precursor was placed in the tube furnace, and phosphorus was placed in the upstream wind direction of the precursor. The molar ratio of the precursor to the phosphorus was 1:9. The tube furnace was heated to 500°C at a heating rate of 6°C / min and kept warm for 5h, and then cooled to room temperature to obtain the coated modified positive electrode material.
[0046] Example 4 First, manganese oxide and sodium hydroxide were mixed in a molar ratio of 2.8:1.3, put into a mortar and ground evenly, and then ball-milled at 700 rpm for 6 hours. Subsequently, the ball-milled material was transferred to a tube furnace under air atmosphere and calcined at a high temperature of 850°C for 20 hours to obtain the positive electrode material.
[0047] Cobalt chloride, 2-methylimidazole and the positive electrode material were mixed in a molar ratio of 1:3:6, dispersed in deionized water and allowed to stand for 18 hours, then centrifuged, and the solid phase was dried to obtain a precursor.
[0048] Nitrogen was continuously introduced into the tube furnace, the precursor was placed in the tube furnace, and phosphorus was placed in the upstream wind direction of the precursor. The molar ratio of the precursor to the phosphorus was 1:7.5. The tube furnace was heated to 450°C at a heating rate of 5°C / min and kept warm for 4h, and then cooled to room temperature to obtain the coated modified positive electrode material.
[0049] Example 5 First, manganese nitrate and sodium carbonate were mixed in a molar ratio of 2.2:1.4, put into a mortar and ground evenly, and then ball-milled at a speed of 900 rpm for 9 hours. Subsequently, the ball-milled material was transferred to a tube furnace under air atmosphere and calcined at a high temperature of 1000°C for 24 hours to obtain the positive electrode material.
[0050] Nickel oxide, 2-methylimidazole and the positive electrode material were mixed in a molar ratio of 1:3:6, dispersed in methanol and allowed to stand for 12 hours, then centrifuged, and the solid phase was dried to obtain a precursor.
[0051] Nitrogen was continuously introduced into the tube furnace, the precursor was placed in the tube furnace, and phosphorus was placed in the upstream wind direction of the precursor. The molar ratio of the precursor to the phosphorus was 1:6. The tube furnace was heated to 300°C at a heating rate of 3°C / min and kept warm for 5h, and then cooled to room temperature to obtain the coated modified positive electrode material.
[0052] Example 6 First, manganese carbonate and sodium hydroxide were mixed in a molar ratio of 3:1.2, put into a mortar and ground evenly, and then ball-milled at 800 rpm for 7 hours. Subsequently, the ball-milled material was transferred to a tube furnace under air atmosphere and calcined at a high temperature of 950°C for 22 hours to obtain the positive electrode material.
[0053] Manganese chloride, 2-methylimidazole and the positive electrode material were mixed in a molar ratio of 1:3:6, dispersed in deionized water and allowed to stand for 16 hours, then centrifuged, and the solid phase was dried to obtain a precursor.
[0054] Nitrogen was continuously introduced into the tube furnace, the precursor was placed in the tube furnace, and phosphorus was placed in the upstream wind direction of the precursor. The molar ratio of the precursor to phosphorus was 1:5. The tube furnace was heated to 400°C at a heating rate of 6°C / min and kept warm for 3h, and then cooled to room temperature to obtain the coated modified positive electrode material.
[0055] Example 7 First, manganese oxide and sodium nitrate were mixed in a molar ratio of 2.5:1.5, put into a mortar and ground evenly, and then ball-milled at a speed of 900 rpm for 8 hours. Subsequently, the ball-milled material was transferred to a tube furnace under air atmosphere and calcined at a high temperature of 800°C for 20 hours to obtain the positive electrode material.
[0056] Cobalt carbonate, 2-methylimidazole and the positive electrode material were mixed in a molar ratio of 1:3:6, dispersed in methanol and allowed to stand for 20 hours, then centrifuged, and the solid phase was dried to obtain a precursor.
[0057] Nitrogen was continuously introduced into the tube furnace, the precursor was placed in the tube furnace, and phosphorus was placed in the upstream wind direction of the precursor. The molar ratio of the precursor to the phosphorus was 1:8. The tube furnace was heated to 500°C at a heating rate of 5°C / min and kept warm for 4h, and then cooled to room temperature to obtain the coated modified positive electrode material.
[0058] Example 8 First, manganese carbonate and sodium hydroxide were mixed in a molar ratio of 2.3:1.4, put into a mortar and ground evenly, and then ball-milled at a speed of 700 rpm for 9 hours. Subsequently, the ball-milled material was transferred to a tube furnace under air atmosphere and calcined at a high temperature of 900°C for 18 hours to obtain the positive electrode material.
[0059] Manganese oxide, 2-methylimidazole and the positive electrode material were mixed in a molar ratio of 1:3:6, dispersed in deionized water and allowed to stand for 18 hours, then centrifuged, and the solid phase was dried to obtain a precursor.
[0060] Nitrogen was continuously introduced into the tube furnace, the precursor was placed in the tube furnace, and phosphorus was placed in the upstream wind direction of the precursor. The molar ratio of the precursor to the phosphorus was 1:9.5. The tube furnace was heated to 450°C at a heating rate of 4°C / min and kept warm for 5h, and then cooled to room temperature to obtain the coated modified positive electrode material.
[0061] The coated and modified positive electrode materials obtained in Examples 1 to 8, the positive electrode material obtained in Comparative Example 1, and the coated and modified positive electrode material obtained in Comparative Example 2 were assembled into batteries respectively: Weigh 0.08 g of coated modified positive electrode material / positive electrode material, 0.01 g of acetylene black (conductive agent), and 0.01 g of PVDF (HSV900, binder), grind them thoroughly, add 0.6 mL of NMP to disperse and mix, slurry evenly, and then draw the slurry on aluminum foil to make sheets. After drying at 85°C with air blowing, cut them into discs with a diameter of 12 mm, and assemble them in a glove box with an argon atmosphere. Use metal sodium sheet as the counter electrode, 1M NaPF6 solution (solvent EC:DEC volume ratio is 1:1) as the electrolyte, and glass fiber (Grade GF / F) as the separator to assemble into a CR2032 button battery.
[0062] Test battery performance: at 25°C, at 1A g -1 The constant current charge and discharge test was carried out at a rate between 2-4.3V. The results are shown in Table 1.
[0063] Table 1 As can be seen from Table 1, the coated and modified positive electrode material provided by the present invention enables the battery to have a higher initial charge capacity and a very high capacity retention rate. The performance of the battery assembled from the final product obtained in Example 1 and Comparative Example 1 is very different, that is, compared with the uncoated positive electrode material, the coated and modified positive electrode material can increase the initial charge capacity of the battery by nearly 25 mA g -1 , the capacity retention rate increased by 8.5%. Comparative analysis of the performance of the battery assembled from the final product obtained in Example 1 and Comparative Example 2 shows that after the phosphorus source is replaced, the initial charging capacity of the battery is not much different, but the capacity retention rate is quite different. Elemental phosphorus is a phosphorus source that is more suitable for vapor deposition to form a phosphide coating layer.
[0064] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A phosphide-coated sodium ion battery positive electrode material, characterized in that: It comprises a positive electrode material matrix and a coating material coated on at least a portion of the surface of the positive electrode material matrix; the chemical formula of the positive electrode material matrix is Na y Mn z O2, 0.67<y<1, 0<z<1; the coating material includes MP, and M is at least one element selected from Ni, Co, and Mn.
2. The phosphide-coated sodium ion battery positive electrode material according to claim 1, characterized in that: The molar ratio of the positive electrode material matrix to the coating material is 1-x:x, 0.3≤x<0.
7.
3. A method for preparing a phosphide-coated sodium ion battery positive electrode material, characterized in that: include: Dispersing a transition metal source, 2-methylimidazole, and a cathode material matrix in a solvent, allowing the mixture to stand, performing solid-liquid separation, and drying the solid phase to obtain a precursor; The chemical formula of the positive electrode material matrix is Na y Mn z O2, 0.67<y<1, 0<z<1; The precursor and elemental phosphorus are sintered under a protective atmosphere to obtain a phosphide-coated sodium ion battery positive electrode material; The transition metal source is at least one of a nickel source, a cobalt source and a manganese source.
4. The preparation method according to claim 3, characterized in that: The nickel source is at least one of nickel chloride, nickel oxide, and nickel carbonate; the cobalt source is at least one of cobalt chloride, cobalt oxide, and cobalt carbonate; and the manganese source is at least one of manganese chloride, manganese oxide, and manganese carbonate.
5. The preparation method according to claim 3 or 4, characterized in that: The molar ratio of the transition metal in the transition metal source, 2-methylimidazole and the positive electrode material matrix is 1:3:
6.
6. The preparation method according to claim 3, characterized in that: The solvent is water or methanol; the standing time is 12 to 24 hours.
7. The preparation method according to claim 3, characterized in that: The molar ratio of the positive electrode material matrix and the phosphorus source in the precursor is 1:5~10.
8. The preparation method according to claim 3, characterized in that: During sintering, the protective atmosphere is continuously introduced; the phosphorus source and the dried solid phase are placed in sequence along the flow direction of the protective atmosphere.
9. The preparation method according to claim 3 or 8, characterized in that: The sintering temperature is 300-500° C.; the sintering time is 2-5 hours; and the sintering heating rate is 3-6° C. / min.
10. A sodium ion battery, characterized in that: It comprises the phosphide-coated sodium ion battery positive electrode material according to claim 1 or 2, or the phosphide-coated sodium ion battery positive electrode material prepared by the preparation method according to any one of claims 3 to 9.
Citation Information
Patent Citations
Sodium-ion battery composite positive electrode material and preparation method thereof, sodium-ion battery positive electrode and sodium-ion battery
CN115275156A